2011
DOI: 10.1177/0748233710393395
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of gold nanoparticles on Salmonella typhimurium bacteria

Abstract: Nanometer-sized gold, due to its beautiful and bountiful color and unique optical properties, is a versatile material for many industrial and societal applications. We have studied the effect of gold nanoparticles on Salmonella typhimurium strain TA 102. The gold nanoparticles in solution prepared using the citrate reduction method is found not to be toxic or mutagenic but photomutagenic to the bacteria; however, careful control experiments indicate that the photomutagenicity is due to the co-existing citrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…In our study, we found a strong mutagenic effect of sodium citrate at a concentration 0.002 % w/v and of Tween 80 at a concentration of 0.008 % w/v. Similar findings were already reported by Wang et al , who have shown that photo-mutagenic effects of gold ENMs are related not only to ENMs but also to citrate ions used as a stabilizer [ 40 ]. Our results have an implication for the ‘safety by design’ approach, indicating that stabilizers with mutagenic potency should not be used in ENM synthesis.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, we found a strong mutagenic effect of sodium citrate at a concentration 0.002 % w/v and of Tween 80 at a concentration of 0.008 % w/v. Similar findings were already reported by Wang et al , who have shown that photo-mutagenic effects of gold ENMs are related not only to ENMs but also to citrate ions used as a stabilizer [ 40 ]. Our results have an implication for the ‘safety by design’ approach, indicating that stabilizers with mutagenic potency should not be used in ENM synthesis.…”
Section: Discussionsupporting
confidence: 90%
“…14 To confirm the latter idea, Wang et al found that gold nanospheres can attach to the membrane of Salmonella typhimurium, but unable to be digested by the bacteria. 15 AgNPs with a concentration range of 1.6-6.25 ug/mL exhibited more than 90% inhibitory effects on biofilm formation of the examined species (Table 1). Generally, the inhibition of the biofilm formation relates to the inhibition of bacterial growth.…”
Section: Discussionmentioning
confidence: 99%
“…A burst of ROS causes, via severe oxidative stress, damage to all the cell's macromolecules, leading to lipid peroxidation, alteration of proteins, inhibition of enzymes, and RNA and DNA damage. At high concentrations the ROS lead to cell death and at low doses cause severe DNA damage and mutations [ 17 , 18 ]. In some cases, where the production of ROS is induced by visible or UV light [ 19 ] the toxicity of NM is photocatalytic.…”
Section: Antimicrobial Nanoparticlesmentioning
confidence: 99%